Image of Bataknese Women in Novel Toba Dreams by TB Silalahi - Yuriska Dewi; Else Liliani; Eka Rahayu Putri; Tri Lande (Britain International for Academic Research (BIAR) Publisher, 2023)
Women are often the object of study in literary works. This is based on the nature of women who tend to be unique and considered attractive, so that most authors choose the perspective of women in representing their works. This research is aimed to describe the image of Bataknese women, the domination of patriarchal culture experienced by Bataknese women, and the decisions women make regarding the treatment of patriarchal domination experienced in the novel Toba Dreams written by TB Silalahi. The research object used is the novel Toba Dreams by TB Silalahi. The research used three data collection techniques namely library techniques, listening or reading techniques, and note-taking techniques. Bataknese female characters in the Toba Dreams novel by TB Silalahi, namely Kristin Sujono, the wife of Sergeant Tebe, Opung Boru, the mother of Sergeant Tebe, Taruli, the daughter of Sergeant Tebe, and Andini, the daughter-in-law of Sergeant Tebe, are interesting things to discuss further. The four figures experienced the domination of patriarchal culture. Many of their lives are decided by the main male characters, namely Ronggur